URGENSI KETELADANAN ORANG TUA DALAM PENDIDIKAN ANAK MENURUT ABDULLAH NASHIH ULWAN DALAM KITAB TARBIYAH AL-AULAD FI AL-ISLAM (STUDI ERA PANDEMI COVID-19) - Anis Nur Lailiyah dan Lauwahatul Izzah (Jurnal Ilmu Pendidikan Islam, 2021)
This study discusses the urgency of exemplariness parents in childrens education according to Abdullah Nasih Ulwan in the book of Tarbiyah al-Aulad fi al-Islam (study of the covid-19 pandemic era). This study aims to determine the urgency of exemplary parents in children's education according to Abdullah Nashih Alwan in the book Tarbiyah al-Aulad fi al-Islam and to find out how important the example of parents in children's education in the covid-19 pandemic era. The type of this research is qualitative research with library method. Primary data sources in the form of the book Tarbiyatul Aulad fil Islam and secondary data sources that serve as auxiliary tools in this research in the form of the book Arrasul al-Muallim, the book Manhaj at-Tabiyah An-Nabawiyah lit-Tifl, and the book Athfalul Muslimin Kaifa Rabba Humun Nabiyul Amin. The data collection technique uses the documentation method while the data analysis technique uses a descriptive method with a content analysis technique approach. The results of this study state that: 1) According to Abdullah Nashih Alwan in his book Tarbiyah al-Aulad fi al-Islam, examplariness parents in childrens education is very important; 2) Exemplariness parents are needed in childrens education in the era of the covid-19 pandemic. Keyword: exemplariness parents, childrens education, and covid-19 pandemic